14-3-3 Proteins Are on the Crossroads of Cancer, Aging, and Age-Related Neurodegenerative Disease - Fan, Xiaolan; Cui, Lang; Zeng, Yao; Song, Wenhao; Gaur, Uma; Yang, Mingyao (International journal of molecular sciences, 2019)
14-3-3 proteins are a family of conserved regulatory adaptor molecules which are expressed in all eukaryotic cells. These proteins participate in a variety of intracellular processes by recognizing specific phosphorylation motifs and interacting with hundreds of target proteins. Also, 14-3-3 proteins act as molecular chaperones, preventing the aggregation of unfolded proteins under conditions of cellular stress. Furthermore, 14-3-3 proteins have been shown to have similar expression patterns in tumors, aging, and neurodegenerative diseases. Therefore, we put forward the idea that the adaptor activity and chaperone-like activity of 14-3-3 proteins might play a substantial role in the above-mentioned conditions. Interestingly, 14-3-3 proteins are considered to be standing at the crossroads of cancer, aging, and age-related neurodegenerative diseases. There are great possibilities to improve the above-mentioned diseases and conditions through intervention in the activity of the 14-3-3 protein family.